2016
DOI: 10.1159/000443484
|View full text |Cite
|
Sign up to set email alerts
|

Urine Calcium and Bone Mineral Density in Calcium Stone-Forming Patients Treated with Alendronate and Hydrochlorothiazide

Abstract: Introduction: The objective was to evaluate the effect of hydrochlorothiazide and alendronate on urine calcium and bone mineral density in calcium stone-forming patients. Material and Methods: A prospective, non-randomized, non-observational comparative study was performed; this study included 111 patients with recurrent calcium stones, divided into 3 groups according to the treatment received. Group 1: 36 patients were treated with alendronate, 70 mg/week; Group 2: 34 patients were treated with alendronate, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…After internalization, bisphosphonates inhibit osteoclasts, preventing them from bone resorption [49]. Many observational and experimental studies have shown a positive association between bisphosphonate use and BMD [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68], and several important randomized trials should be highlighted. The Fracture Intervention Trial (FIT) was originated to investigate the effect of alendronate on the frequency of fractures in postmenopausal women with low bone mass, although they also investigated the effect on BMD and showed that alendronate increased BMD at several sites [60][61][62].…”
Section: Bisphosphonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…After internalization, bisphosphonates inhibit osteoclasts, preventing them from bone resorption [49]. Many observational and experimental studies have shown a positive association between bisphosphonate use and BMD [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68], and several important randomized trials should be highlighted. The Fracture Intervention Trial (FIT) was originated to investigate the effect of alendronate on the frequency of fractures in postmenopausal women with low bone mass, although they also investigated the effect on BMD and showed that alendronate increased BMD at several sites [60][61][62].…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…Most studies involving thiazides and BMD were conducted in patients with kidney stones or in postmenopausal women, all showing a positive effect of thiazide diuretics on BMD [51,227,[245][246][247][248][249][250][251][252]. For example, a retrospective analysis including 299 kidney stone patients showed an increase in BMD after 1 year of treatment with hydrochlorothiazide [245], and similar results were found in a prospective study, but only after 2 years of treatment [51]. An increase in BMD and a decrease in bone turnover markers with thiazides was shown in an observational study of 636 post-menopausal women [247].…”
Section: Thiazide Diureticsmentioning
confidence: 99%
“…84,85 Dietary recommendations for stone reduction including a low sodium and normal calcium diet have also been shown to improve BMD. 86 Thiazide diuretics also reduce urinary calcium levels, decrease stone recurrence, 867 improve BMD in stone formers 85,87,88 and reduce the risk of hip fractures. 89 In addition, alkali citrate therapy has a positive effect on both stone recurrence and bone health by reducing bone resorption and buffering acid production.…”
Section: Treatment Of Calcium Stone Formers With Either a Thiazide Di...mentioning
confidence: 99%
“…Among various types of stones, calcium oxalate stones are the most common urinary tract stones [2]. Various factors, the most important of which are stone size and location, are considered in treating patients with urinary tract stones [3]. Patients are examined by obtaining their history and carrying out diagnostic radiology such as sonography.…”
Section: Introductionmentioning
confidence: 99%